Hunters of the “Mediterranean Triad”: persistent and intensive exploitation of faunal resources during the Late Middle Pleistocene at Cueva del Ángel (Lucena, Spain) - Solano-García, José A.; Moigne, Anne-Marie (Frontiers in Environmental Archaeology, 2025)
This study focuses on the Neanderthal subsistence strategies at Cueva del Ángel, a site in southern Spain with a stratigraphic sequence from the Late Middle Pleistocene. Using zooarchaeological and taphonomic methodologies, we conducted a diachronic analysis of over 3,500 faunal remains to explore the exploitation patterns of medium- and large-sized ungulates. Results reveal a systematic and intensive exploitation of large mammals, particularly horses, red deer, and large bovids, with an emphasis on high-energy resources, such as meat and marrow. The anatomical representation and fragmentation patterns suggest selective hunting strategies and an intensive use of animal resources. Complementary resources, such as small game, were also exploited, potentially reflecting adaptive responses to increase predictability and minimize risks. The results align with other Eurasian sites from this period, emphasizing the persistence of large-game hunting as a core subsistence strategy, supplemented by diversified resources to mitigate risk. These findings underscore a consistent and flexible approach to resource management over time, highlighting the adaptability of Neanderthal subsistence strategies in Mediterranean ecosystems.